Alat Peraga Kontrol Dan Monitoring Lampu Sorot Lapangan Perwira Angkasa di Politeknik Penerbangan Indonesia Curug - Lado, Amsal Yanuardi; Widiarto, Hendro; Samanhudi, Asep (Langit Biru: Jurnal Ilmiah Aviasi, 2020)
The Curug Indonesian Aviation Polytechnic Cadets have duties on this campus, namely studying and becoming a guard cadet. The guard cadets have the duty to attend the cadets at apples or eat and write the lights in the barracks or in the field. In the field of the Indonesian Aviation Polytechnic, Curug has a field for cadets called Perwira Angkasa. In the field there are 4 spotlight poles that are used for lighting the field. Conditions like Taruna. Keeping field lights for Space Officers must go to every panel in the Space Officers field. With the distance between the guard Room and the Space Officer field as far as 2 kilometers. When the weather is unfriendly like rain and darkness, then there cadets have difficulty turning on the lights. With these conditions, the authors will make a props for the controller and monitoring lights via website. Some of the tools used by the author: Wemos D1 Microcontroller, Relay, AC712 Sensor, Logic Level Converter, Miniature Circuit Breaker (MCB), and Spotlights. From the results of the props that are made, it can facilitate the task ofcadets to make lamps, besides being useful for developing technology in the Microcontroller and adding knowledge in the Control System course